Parent Employment and School/Daycare Decisions among Parents of Young Children with Type 1 Diabetes - Herbert, Linda J. (Child Health Care, 2016)
This study explored the employment and school/daycare experiences of parents of young children with type 1 diabetes (T1D). Parents (n=134) of young children with T1D (ages 1–6) responded to open-ended questions. Responses were systematically reviewed to identify themes. Four parent employment themes were identified: work cessation/reduction, employment flexibility, significant career impact, and financial pressure. Three school/daycare attendance themes were identified: school/daycare structure and setting, previous experience with T1D, and school/daycare importance. Insulin regimen, child age, and family income were related to parents’ decisions. Parents may benefit from clinical programs that assist them with employment and school/daycare decisions.